exploding cluster dynamics probed by XUV fluorescence - M Negro; H Ruf; B Fabre; F Dorchies; M Devetta; D Staedter; C Vozzi; Y Mairesse; S Stagira (New Journal of Physics, 2014)
Clusters excited by intense laser pulses are a unique source of warm dense matter, that has been the subject of intensive experimental studies. The majority of these investigations concern atomic clusters, whereas the evolution of molecular clusters excited by intense laser pulses is less explored. In this work we trace the dynamics of ${\rm C}{{{\rm O}}_{2}}$ clusters triggered by a few-cycle $1.45\;μ {\rm m}$ driving pulse through the detection of XUV fluorescence induced by a delayed 800 nm ignition pulse. Striking differences among fluorescence dynamics from different ionic species are observed.